Discrete analytic continuation of a (p, q)- analytic function - Ahmad Khan, Mumtaz; Najmi, M. (Pro Mathematica, 2000)
In this paper a method is devised for the continuation into the discrete plane Q' of functions defined on the positive half-axes and the properties of continuation operator discussed.